Recent advances in molecular biology research of a rice pest, the brown planthopper - Yan-yuan BAO; Chuan-xi ZHANG (Journal of Integrative Agriculture)
The brown planthopper, Nilaparvata lugens Stål, has become a major threat in tropical Asian and China since the rice green revolution of the 1960s. Currently, insecticide application remains the primary choice for controlling this rice insect pest, but heavy use of insecticides poses dangerous risks to beneficial natural enemies and pollinators, and stimulates N. lugens reproductivity, and has caused a resurgence of the pest in the major rice-planting regions throughout Asia. Achieving the long-lasting goal of sustainable management of N. lugens requires understanding of the molecular basis of outbreaks of the pest and the development of environment-friendly pest-control strategies. Here, we review the recent molecular advances in N. lugens research on the aspects of its endosymbionts, virus transmission, insecticide resistance, and interaction between N. lugens and rice plants. We also put forward further research directions that may shed some lights on management of the rice pest.